2010
DOI: 10.4314/ajbr.v11i2.50714
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal and economic value of spondias mombin

Abstract: This article reviewed the folk medical value of Spondias mombin with the correlated research findings on the uses of Spondias mombin. Most of the folk uses had been scientifically proven in most of the regions where those beliefs are based. The plant was described with habitat, the local uses including the uses of its parts mentioned. We reviewed the ethnomedicinal uses, the biological activities and the phytochemistry of Spondias mombin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 12 publications
2
74
0
6
Order By: Relevance
“…The concoction from the leaves is widely used for the treatment of diarrhea, dysentery, stomach ache and inflammation (Ayoka et al 2008). Various studies have shown that the leaf extracts possess pharmacological properties such as anti-inflammatory, antimalaria, antibacterial, anxiolytic, antioxidant and antiviral effects (Ayoka et al 2008). Despite the ethnobotanical usage of the plants, no biological activity from its essential oil has been reported in literature to support this claim.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The concoction from the leaves is widely used for the treatment of diarrhea, dysentery, stomach ache and inflammation (Ayoka et al 2008). Various studies have shown that the leaf extracts possess pharmacological properties such as anti-inflammatory, antimalaria, antibacterial, anxiolytic, antioxidant and antiviral effects (Ayoka et al 2008). Despite the ethnobotanical usage of the plants, no biological activity from its essential oil has been reported in literature to support this claim.…”
Section: Introductionmentioning
confidence: 94%
“…Other common names are Iyeye (Yoruba), ngulungwu (Igbo), pauda tapera (Brazil) and ubo (Peru). The concoction from the leaves is widely used for the treatment of diarrhea, dysentery, stomach ache and inflammation (Ayoka et al 2008). Various studies have shown that the leaf extracts possess pharmacological properties such as anti-inflammatory, antimalaria, antibacterial, anxiolytic, antioxidant and antiviral effects (Ayoka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…from the flowers and leaves) is taken to relieve stomach aches, biliousness, urethritis, cystitis, as well as to ameliorate inflammation of the eye and/or throat (Ayoka et al, 2008). Lastly, the decoction of the astringent bark has been used as an emetic, a remedy for diarrhea, dysentery, and hemorrhoids, and also as a treatment for gonorrhea (Ayoka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the decoction of the astringent bark has been used as an emetic, a remedy for diarrhea, dysentery, and hemorrhoids, and also as a treatment for gonorrhea (Ayoka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A helps to maintain good sight and prevents eye diseases. Both the vitamins have antioxidant property [28]. Vitamin B (folic acid) were occurred in traces.…”
Section: Estimation Of Vitaminsmentioning
confidence: 99%